Analysis Factors Related to Primary Dysmenorrhea in Adolescent Girls at MTS Negeri Surabaya II - Stefani Angel; Ni Ketut Alit; Retnayu Pradanie (Pediomaternal Nursing Journal, 2016)
Introduction : Dysmenorrhea or menstrual pain is a common problem complained of by the teens that can interfere withdaily activities and productivity adolescents. This study was aimed to analyze factors associated with the incidence ofprimary dysmenorrhea (nutritional status, physical activity and stress) in adolescent girls at MTs Negeri SurabayaII. Methods : This research used is a cross-sectional sample of 49 female students of class VIII. Sampling was done bysimple random sampling technique. The independent variable in this study is the nutritional status, physical activity andstress. While the incidence of primary dysmenorrhea is the dependent variable. Data were obtained through aquestionnaire and analyzed by using Spearman rank with a significant level of p <0.05. Results : The results of this studyfound that nutritional status is not associated with the incidence of primary dysmenorrhea (p = 1.00), physical activityassociated with the incidence of primary dysmenorrhea (p = 0.003), and stress also has a relationship with the incidenceof primary dysmenorrhea (p = 0.001). Discussion: The nutritional status does not increase the risk of incidence ofprimary dysmenorrhea in adolescents, whereas physical activity and stress can increase the risk of incidence of primarydysmenorrhea in adolescent girls at MTs Negeri Surabaya II.